Evaluasi Pelaksanaan Dalam Kajian Biaya Lebih Pada Pekerjaan PLTU dengan Jenis Kontrak EPC: Studi Kasus Pekerjaan PLTU Oleh PT.X - Haryono, Sony; Silviana, S; Setyo Huboyo, Haryono (Jurnal Profesi Insinyur Indonesia, 2023)
Coal Fired Steam Power Plant (CFSPP) Project is a complex project that requires multidisciplinary knowledge in its implementation. As a result, cost overruns often occur in its implementation. In Indonesia, most power plant projects are using EPC contracts (Engineering, Procurement, and Construction). The contractor is fully responsible for any failures that may occur during the work implementation period. The aim of this study is to compare the realization of completion costs for CFSPP projects with Bill of Quantity (BoQ) and the factors that influence deviations. This research was conducted qualitatively based on the data obtained. Deviations are calculated based on the difference between completion costs and BoQ. Discussions and interviews were conducted with Project Managers and Site Commercial and Risk Managers who were directly involved in construction phase to determine the causes of cost overruns. The result is that the actual cost incurred in the CFSPP project is 3x the cost listed in BoQ. There are cost overruns in each work group including Civil Works, Mechanical Works, Electrical Works and Others Works. Indirect cost realization is 29.84% of total completion cost. The factors that influence cost overruns are: (i) Contractors do not understand the details of the work to be done, (ii) Changes in design and (iii) Realization volume exceeds initial planned volume. The results of this study are expected to be input in preparing owner estimate for CFSPP projects and adding new risk factor lists in CFSPP during construction phase.